Using Oyster Shells for Customized 3-D Structures for Monitoring Ecosystem Shifts on Ascidians Diversity - Marques, Luisa; Teixeira, Guilherme; Calado, Ricardo; Lillebø, Ana Isabel (Frontiers in Marine Science, 2022)
Biofouling communities are broadly distributed and there is a growing need to understand, monitor, and prevent their dispersal and colonization. Ascidians are a major group of fouling organisms but have remained poorly studied in this context. Furthermore, the search for improved sustainable practices regarding shipping networks, biofouling management, treatments, and monitorization has made headway rapidly. The present study surveyed and established a baseline for the ascidian biofouling community in a coastal lagoon, by operationalizing the concept of artificial substrate units (ASU) through a customized 3-D unit with the shape of a triangular-based pyramid, a nature-based structure that simulates natural habitats, made with oyster shells sourced from local aquaculture farms. The ASU were grouped into a five-replicate star-shaped, to be collected at each sampling moment. Throughout the 295 days (from May to December of 2020) of the present study covering five different locations of Ria de Aveiro (Portugal) coastal lagoon, a total of 12 species of ascidians were collected. While Ascidiella aspersa, Microcosmus sp., and Molgula sp. 1 were registered in all the locations surveyed, the remaining nine ascidian species were dominant only in specific locations of the coastal lagoon. Values of total abundance presented an overall increasing trend in all locations surveyed, with maximum values corresponding to summer periods. Two locations (Oyster Farm and Integrated Multi-Trophic Aquaculture Farm) recorded the highest abundance values. The present findings demonstrated that the ASU employed using oyster shells, a widely available co-product of oyster farming, can be considered an efficient support structure for short- or long-term monitoring of the ascidian community, as well as fouling communities in general. Hydrodynamics, seasonality, and nutrient-enriched waters were the main contributors to the establishment of ascidians. For the first time, Clavelina lepadiformis and A. aspersa were collected and reported in coastal waters of mainland Portugal. While preventing the settlement of fouling communities can be extremely difficult, an improved understanding of existing communities of these organisms can undoubtedly contribute to the development of improved management practices to control them. An updated list of all ascidian species recorded to date from coastal waters of mainland Portugal is also presented.